9+6x=-18x

Simple and best practice solution for 9+6x=-18x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+6x=-18x equation:


Simplifying
9 + 6x = -18x

Solving
9 + 6x = -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
9 + 6x + 18x = -18x + 18x

Combine like terms: 6x + 18x = 24x
9 + 24x = -18x + 18x

Combine like terms: -18x + 18x = 0
9 + 24x = 0

Add '-9' to each side of the equation.
9 + -9 + 24x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 24x = 0 + -9
24x = 0 + -9

Combine like terms: 0 + -9 = -9
24x = -9

Divide each side by '24'.
x = -0.375

Simplifying
x = -0.375

See similar equations:

| -1.5x+5.7=.5x+.3 | | 2/5x-3/c | | -5x+20+2x+12=5 | | -4y-12=142 | | 6x-36=12 | | (81m*6)1/2 | | (7/5)*(3/1)= | | 12+3(x+2)=-63 | | ln(x^2)=3.891 | | (2x+15)+(x-12)=180 | | 4x^4+20x^2-56=0 | | 5+-3=17 | | -8+4x+4x=40 | | 64-y=130 | | (1/2)2x-5=x-9 | | 7x-8-6x=2 | | 3u^4+33u^2+54=0 | | 7x-6-5x=12 | | (2x+15)-(x-12)=180 | | 8.3=-0.6+11.3 | | 6=-3x-2x+6 | | 32+8y=16y+16 | | 5(6y-4)-(-8y+4)= | | 36/7*4/x=6 | | 0=5x-4x+1 | | a^4-3a^2-18=0 | | 3/5a=94 | | Y+-5=14 | | 10x/3y=1 | | 7-7x=12-7x | | 3+x-(3*x)=1 | | 3a^2+14=13a |

Equations solver categories